2018
DOI: 10.1007/s00404-018-4917-z
|View full text |Cite
|
Sign up to set email alerts
|

Disadvantages of a weight estimation formula for macrosomic fetuses: the Hart formula from a clinical perspective

Abstract: PurposeSonographic fetal weight (FW) estimation to detect macrosomic fetuses is an essential part of everyday routine work in obstetrics departments. Most of the commonly used weight estimation formulas underestimate FW when the actual birth weight (BW) exceeds 4000 g. One of the best-established weight estimation formulas is the Hadlock formula. In an effort to improve the detection rates of macrosomic infants, Hart et al. published a specially designed formula including maternal weight at booking. The useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…On one hand, normal-weight fetuses are massively overestimated, and on the other hand, fetuses with the highest birth risk (BW > 4500 g) will not be detected. The same problem applies to the formula for macrosomic fetuses published by Hart et al in 2010 [22,23].…”
Section: Discussionmentioning
confidence: 93%
“…On one hand, normal-weight fetuses are massively overestimated, and on the other hand, fetuses with the highest birth risk (BW > 4500 g) will not be detected. The same problem applies to the formula for macrosomic fetuses published by Hart et al in 2010 [22,23].…”
Section: Discussionmentioning
confidence: 93%
“…In recent years several EFW prediction models have been developed, but none of these models were practiced in routine clinical applications or recommended according to the current guidelines. Hadlock’s formula is still thus far one of the best-established weight estimation formulas and the one most widely used in everyday routine work, despite recent studies indicating potential ways to decrease MAPE, the especially in macrosomic fetuses and other deviant cases [ 8 , 23 ]. Although, due to the drastic difference in the number of participants, the MAPE in this study was slightly higher than that calculated by Konwar [ 8 ] or Weiss [ 23 ] (5.79% for DNN estimation and 6.46% for Hadlock’s formula), the DNN model still predicted the EFW more accurately compared to the Hadlock’s formula.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 Likewise, Hadlock's formula remained the top choice for LGA detection. 52,55,56 It has been suggested that the accuracy of fetal weight estimation may have reached a maximum using traditional biometric parameters. 57 Significant advances can probably only come from new ultrasonography technology.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…performed better than others if the presence of a brain-sparing effect was identified 53,54 . Likewise, Hadlock's formula remained the top choice for LGA detection 52,55,56 . It has been suggested that the accuracy of fetal weight estimation may have reached a maximum using traditional biometric parameters 57 .…”
Section: How To Establish a Chinese Fetal Growth Standardmentioning
confidence: 99%